2019
DOI: 10.37706/iconz.2019.176
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Muzaki Use and Receive Zakat Payment Platform

Abstract: The purpose of this paper was to determine the factors that affect muzaki receive and use the platform to pay zakat. The method used in this research is a descriptive method with a quantitative approach to muzaki ever to its digital pay zakat institutions with a total of 100 respondents. The results show that the performance expectations, expectations of the business have a high influence on behavioral intentions muzaki in receiving and using the online zakat payment platform and condition of the facility, beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…However, the growth of technology influences the behavior of humans, particularly in fulfilling zakat performance, which is better by digitalization. Previous research that focused on online fundraising has different results and methods (Ahmad et al , 2014; Mahri et al , 2019; Ninglasari and Muhammad, 2021; Yahaya and Ahmad, 2019). Research conducted by Ninglasari and Muhammad (2021) shows that digitalization has the benefits of collecting, managing and distributing zakat funds during COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the growth of technology influences the behavior of humans, particularly in fulfilling zakat performance, which is better by digitalization. Previous research that focused on online fundraising has different results and methods (Ahmad et al , 2014; Mahri et al , 2019; Ninglasari and Muhammad, 2021; Yahaya and Ahmad, 2019). Research conducted by Ninglasari and Muhammad (2021) shows that digitalization has the benefits of collecting, managing and distributing zakat funds during COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some research that has been conducted showed various results with different methods and approaches (Ahmad et al , 2014; Mahri et al , 2019; Ninglasari and Muhammad, 2021; Yahaya and Ahmad, 2019). This research used an extended UTAUT approach to see the behavioral intention of paying zakat through digital platforms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…al., 2021;Harun & Ab Rahman, 2021). Therefore the use of the zakat platform is still in effective (Mahri et, al., 2019).…”
Section: Introductionmentioning
confidence: 99%